Relevance of silica surface morphology in ampyra adsorption: insights from quantum chemical calculations - Noseda Grau, Emilia (2019)
Theoretical calculations are performed using the Vienna Ab-initio simulation package (VASP) to understand the mechanisms that control the adsorption of Ampyra drug on the different crystallographic planes of bcristobalite: the hydroxylated (111) and (100) surfaces. The Ampyra-silica interaction is most favored on the (100) surface where the entire ring of the molecule interacts with the surface while on the (111) face, lesser exchange and fewer non-polar atoms are involved. Calculations show that the interactions mainly occur at the interface between the Ampyra and the closest silanol groups, according to the formation of the Hbonding interactions. The results indicate that the H-bonds have an important influence on the adsorption of the Ampyra. In consequence, adsorption on the (111) surface is observed to a lesser extent than on the (100) surface according the smaller hydroxyl density.